Perancangan Dan Analisis Solar Pv Battery Charger Menggunakan Topologi Buck-Boost Converter - Ferdy Ultra Sony; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Excessive use of fossil energy has a bad impact on humans and the environmentals. Generally, the use of fossil energy has now entered a critical phase because of the lack of availability of fossil energy resources. Indonesia is located in the equatorial region that gets sunlight all the year round. Solar energy is a primary energy that offers the opportunity to replace fossil energy. Solar energy is processed by using a solar panel modules system and can be stored in the batteries. The source voltage that connected to the battery must first be stabilized using a DC converter. In this article, the design and simulation of solar PV battery charger using buck-boost converter topology with MATLAB-simulink software is presented. Solar PV battery charger is designed with an output voltage of 16.8 V and a current of 6 A, which will charge the lithium-ion battery (li-ion) where it has a nominal voltage of 14.8 V with a capacity of 20.8 Ah.Keywords—solar PV battery charger, buck-boost converter, lithium-ion battery, MATLAB-Simulink